Utilization of Near Field Communication Technology for Loyalty Management - Ferina Ferdianti; Yusuf Triyuswoyo; Dewi Agushinta R. (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Near Field Communication (NFC) is one of wireless technology developed at this time. We can use a mobile phone to do many transactions with NFC. Mobile developments have created to provide convenience for users in all aspects. However, at this time the function of NFC just limited for payment and micropayment. Beside it, there are assets that support to increase sales with attention of loyality management system. In this system, discounts or prizes are given based on data mining for every transaction customers. This loyalty management has three concepts. Those are Frequency, Recency and Quantity (FRQ). The goals are minimizing the cost, making purchase process faster, and managing data obtained through the NFC technology more simple. The result of this paper is the procedure to use data mining of NFC for loyalty management and designing system using Unified Modeling Language approach.